The Shield of San Fernando - Salaverry García, Oswaldo (1995)
The representative shields from the Faculty of Medicine are described from their onset to nowadays, comparing them with their original forms and evaluating their fidelity with the first symbols. A new shield which gathers the corrections and recreates the Hipolito Unanue's original design is proposed.